ショウワキチ オヨビ シラセ センジョウ オケル チジョウ オゾン ノウド ノ レンゾク カンソク - 青木, 周司; アオキ, シュウジ; Aoki, Shuhji (1997)
P(論文) 昭和基地における地上オゾン濃度の連続観測は1988年2月に開始された。オゾン濃度の日変化は南極の春の時期だけに見られ, 他の季節には観測されなかった。日変化の最大は9月と10月に現われており, 平均振幅の最大値は2ppbvであった。日変化の最高値は早朝に現われ, 最低値は午後に現われている。日平均オゾン濃度はきれいな季節変化を示しており, 最高濃度は冬に, 最低濃度は夏に現われ, 振幅は約20ppbvであった。季節変化の最低濃度は毎年ほぼ同じ値であったが, 最高濃度は年々変化していた。最高濃度が比較的高かった年は1988年と1990年であり, 低かった年は1989年, 1991年および1992年であった。このような最高濃度の変化は南極域の大気循環の変動によるものではないかと推定される。昭和基地では毎年8月から10月にかけてオゾン濃度が数日間ほぼゼロになる現象が現われることが見い出された。このような地表付近でのオゾン破壊現象は南極大気の光化学反応が関係していると推定されている。 Continuous measurements of lower tropospheric ozone have been made at Syowa Station, Antarctica, since February 1988. The diurnal variation of the lower tropospheric ozone was observable only for the austral spring; variation could not be seen in the other seasons. The average amplitude of the diurnal variation reached a maximum value of about 2ppb at most in September and October. The maximum and minimum concentrations of the diurnal variations appear before sunrise and in the afternoon, respectively. The daily mean ozone concentrations showed a clear seasonal cycle with maximum concentration in winter and minimum concentration in summer, and mean amplitude of about 20ppb. Minimum concentrations of the seasonal cycle were almost the same for each year but maximum concentrations were variable from year to year; higher concentrations appeared in 1988 and 1990 and lower concentrations in 1989,1991 and 1992. These variations might be ascribed to changes of the atmospheric circulation in the Antarctic. It was found that extremely low values of lower tropospheric ozone with periods of a few days appeared sporadically between August and October every year. The ozone destruction phenomenon should be related to the photochemical processes in the Antarctic atmosphere. departmental bulletin paper